1976
DOI: 10.1002/app.1976.070200303
|View full text |Cite
|
Sign up to set email alerts
|

An infrared technique for the quick analysis of cotton–polyester blends

Abstract: SynopsisThe details of an infrared technique standardized to analyze cotton-polyester blends of different compositions are reported. It is observed that particle size plays a very important role in the peak intensity of the 1725 cm-' band (C=O stretching) in polyester, the absorption band recommended for analysis of cotton-polyester blends. However, the product of the band width and peak intensity is found to be dependent on particle size to a lesser extent and hence is a more reliable parameter in the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The band at 1713 cm −1 refers to the carbonyl group C=O stretch, and C-O stretch and O-H deformation have been identified at 1413-1472 cm −1 [26,27]. The bands in the region 877 cm −1 are associated with the benzene ring [28]. A complementary band detected in the region 712 cm −1 can be attributed to the angular deformation of (CH2)n [26].…”
Section: Evaluation Of Surface Modificationmentioning
confidence: 98%
“…The band at 1713 cm −1 refers to the carbonyl group C=O stretch, and C-O stretch and O-H deformation have been identified at 1413-1472 cm −1 [26,27]. The bands in the region 877 cm −1 are associated with the benzene ring [28]. A complementary band detected in the region 712 cm −1 can be attributed to the angular deformation of (CH2)n [26].…”
Section: Evaluation Of Surface Modificationmentioning
confidence: 98%
“…The increase in the amorphousity especially at the end of exposure leading to an increase in the exhaustion and diffusion of the dye inside the fabric pores whereas; uv/ozone exposure of the samples districts the dye accumulation and hence increases the levelness of dyeing. For polyester fabric the observed slight increase in (K/S) and (L) values by prolonging uv/ozone exposure, is due to the increase in the polarity of these treated fabrics, which results from the increase in the intensity of different functional groups of these fabrics by prolonging exposure to uv/ozone leading to an increase in their availability for linkage with the reactive species of each dye applied, and hence increasing dye up-take but to an extent depends on the dye type (Bhama Iyer P., et al, 1976). While the improvement in (K/S) and (L) values by prolonging uv/ozone exposure of blend (wool/polyester) fabrics especially at the end of exposure, can be explained in view of the fact that (Ibrahim, S. F., Ph.D. Thesis, 2003), there is a remarkable increase in the peak intensity values of the different functional groups which characterize such blend especially at the end of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated correlation coefficient is 0.9998, which is highly significant. Bhama Iyer et al [6] observed that particle size plays a very important role in the peak intensity of the Cs tretching band of the carbonyl group in polyester, the absorption band recommended for analysis of cotton/ polyester blends. The absorbance of the C~ band versus composition does not yield a straight line.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of non-overlapping absorption bands in IR spectra makes such analysis easier and more reliable. Various examples of quantitative determinations of fiber blends have been reported, including cotton/ dacron by O'Conner [ 10], wooUterylene by Clark and Hickie [3], cotton/polyester by Bhama Iyer et al [6], and acrylic/wool by Soosamma et al [ 12]. In this paper, we report a simple technique based on an ttt method for quantitative analysis of ramie/acrylic blends.…”
mentioning
confidence: 94%